A Possible Correlation Among Different Disease Activity Parameters and Functional Status in Patients with Ankylosing Spondylitis - Saliha EROĞLU DEMİR and Ebru AYTEKİN and Levent ÖZGÖNENEL and Aylin REZVANİ and Yasemin PEKİN DOĞAN and; SAYINER ÇAĞLAR and; l ÖZARAS and; l ÇAĞLAR OKUR and; an AYDIN and; TÜTÜN and; l. (Archives of Rheumatology, 2013)
Objectives: The primary aim of this study was to assess the possible relationship among the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), the Bath Ankylosing Spondylitis Functional Index (BASFI), and two Ankylosing Spondylitis Disease Activity Score (ASDAS) including the C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) scores in patients with ankylosing spondylitis (AS). The secondary aim was to investigate gender differences in terms of disease activity scores and functional status. Patients and methods: Five hundred patients (158 females, 342 males; mean age 37.2±9.9 years; range 15 to 70 years) with AS were enrolled. Disease activity was assessed through the BASDAI, ASDAS-CRP and ASDAS-ESR, while functional status was evaluated by the BASFI. Results: The mean BASDAI, ASDAS-CRP, ASDAS-ESR, and BASFI scores were 3.71±2.26, 1.65±0.83, 2.59±1.12, and 2.68±2.38, respectively. The BASDAI and ASDAS-ESR values of the female patients with AS were significantly higher than those of the males. The BASDAI and BASFI were significantly associated with the two ASDAS scores. According to the BASDAI, 46.6% of the patients had a high disease activity and had significantly higher values in terms of symptom duration, compared to those with lower BASFI, and two ASDAS scores. The ASDAS-CRP scores of the disease activity indices were similar in both genders. Conclusion: Our study results suggest that the two ASDAS scores are significantly associated with the disease activity and functional status. We believe that using ASDAS-CRP indices is more suitable for a disease activity parameter in further studies involving patients with AS in both genders, however not analyzing gender differences.